Developing Communication Competencies of Library Professionals Through Semiotics Theory Approach in the Contemporary Information System - Saha, Tumpa; Barui, Tapan (Access: An International Journal of Nepal Library Association, 2023)
Purpose: The purpose of this paper is to identify the relationship between semiotics theory and communication theory and focus on how semiotics could act as a useful tool to play a big role in the development of communication competencies of library professionals in the contemporary information system. Design/ Methodology/ Approach: The study is fundamentally analytical and qualitative in nature. The analysis of semiotic theory and communication theory is done one by one. In this paper, we use the semiotics theory approach in library services and propose an illustrative library classification list based on Dewey Decimal Classification (DDC) for the development of an effective communication competency as well as improve the visual literacy skills of library professionals. Findings: After the study, we find out that the semiotic theory is a general and unrestricted model of sign whereas communication theory is also a general and unrestricted model of communication which is useful for every field of study including the LIS field. Semiotics theory and Communication theory both are very similar and Semiotics build a strong communication competency and improve the visual literacy skills of library professionals. Practical implications: This study will be helpful for library professionals to develop their competencies according to the needs of the hour. Users will be more beneficial and attracted to the library than the formal mode of communication. Those people who cannot communicate in an unknown language and are unable to articulate language can also communicate easily through the visual mode of communication with the help of semiotics. Originality: This paper is the first to combine the theories of communication and semiotics within the context of the competency development of library professionals.